The Use of QRIS in MSMEs in Cilegon City - Yunita , Adelia (Jurnal Keuangan dan Perbankan (KEBAN), 2023)
Changes in people's lifestyles and advances in the development of financial technology (financial technology) currently have an impact on people's desire for fast, precise, and safe digital payment instruments Seeing the current growing trend, several marketplaces are starting to use QR-Code as a payment method. The system changed the habits of many people from initially making cash payments to cashless. This is used by micro, small and medium enterprises (MSMEs) as a tool for simple and complicated financial transaction processes. The number of MSME players in Cilegon City is currently officially recorded at 18,117 business actors in 2023. This number is so large that the contribution of MSMEs to the economy of Cilegon City is felt, especially in terms of new workers. Therefore, this study is to determine the perception of MSME actors in using QRIS the methodology of this research is quantitative descriptive with saturated sampling techniques, the population in this study is 50 MSME actors in Cilegon City with a total sample of the population. The results in the perception of expediency get a percentage result of 72.2%, then in the perception of ease of getting 76.6% and the perception of risk get 69% so that it can be concluded that MSME actors feel helped by the payment system using QRIS